2021
DOI: 10.1039/d1sc04445a
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the generation of broad spectrum antibiotics with the addition of a positive charge

Abstract: Antibiotic resistance of Gram-negative bacteria is largely attributed to the low permeability of their outer membrane (OM). Recently, we disclosed the eNTRy rules, a key lesson of which is that...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 95 publications
(190 reference statements)
2
22
0
Order By: Relevance
“…More recently, a Monte Carlo pathway search (MCPS) method was described that used a combination of Dijkstra's algorithm and Monte Carlo sampling to obtain an initial path that was used for bias-exchange US simulations. 14 The elevated temperature for the orthogonal degrees of freedom in the TASS formalism enables one to recover the accurate free energy at the system temperature along the CV(s) of interest with improved convergence. 16 For the present system, the center of mass distance between CIP and OmpF projected along the z-axis was selected as the principal CV.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a Monte Carlo pathway search (MCPS) method was described that used a combination of Dijkstra's algorithm and Monte Carlo sampling to obtain an initial path that was used for bias-exchange US simulations. 14 The elevated temperature for the orthogonal degrees of freedom in the TASS formalism enables one to recover the accurate free energy at the system temperature along the CV(s) of interest with improved convergence. 16 For the present system, the center of mass distance between CIP and OmpF projected along the z-axis was selected as the principal CV.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…As in case of US, the initial configurations for the TASS simulations can be obtained from a previous steered MD simulation. More recently, a Monte Carlo pathway search (MCPS) method was described that used a combination of Dijkstra’s algorithm and Monte Carlo sampling to obtain an initial path that was used for bias-exchange US simulations . The elevated temperature for the orthogonal degrees of freedom in the TASS formalism enables one to recover the accurate free energy at the system temperature along the CV(s) of interest with improved convergence .…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Richter et al . 21 identified the presence of a primary amine, flexible bond number (5 or less) and globularity (describing molecular shape), as key features to predict the accumulation of antibiotics in Gram-negative bacteria 22 . Predictive rules of efflux inhibition and avoidance were also identified 23 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Incorporating the aforementioned insights into structure/ligand-based drug discovery approaches to improve existing antibiotics is a possible way forward. In fact, it was recently demonstrated that introducing an amine moiety into antibacterials such as 6DNM, Ribocil-C, and Debio-1452 results in an extended activity spectrum of these antibiotics from Gram-positive to Gram-negative bacteria. The same was studied in computational investigations that indicated the role of the interactions of the amine group with the negatively charged residues of the constriction loop . Certainly, molecules that have been screened as potent inhibitors in in vitro binding assays but have failed in antimicrobial assays can also be considered as possible candidates for additional rounds of assessment and redesign.…”
Section: Understanding Antibiotic Permeation Through Bacterial Nanoporesmentioning
confidence: 99%
“…25 was studied in computational investigations that indicated the role of the interactions of the amine group with the negatively charged residues of the constriction loop. 28 Certainly, molecules that have been screened as potent inhibitors in in vitro binding assays but have failed in antimicrobial assays can also be considered as possible candidates for additional rounds of assessment and redesign. The eNTRy criteria may be incorporated at various phases of drug development, for instance, during the hit-to-lead stage, in the lead optimization, or within the virtual drug design workflow.…”
Section: ■ Introductionmentioning
confidence: 99%